Nano nickel-based catalyst as well as preparation method and application thereof

Through the continuous liquid phase hydrogenation reaction of nano nickel-based catalyst and gas-liquid high-efficiency disperser, the problems of low conversion of 4,4'-diaminodiphenyl ether and poor catalyst stability in the prior art are solved, and high efficiency and environmental protection are achieved The preparation process improves the quality and production efficiency of the product.

CN119215918APending Publication Date: 2024-12-31CNOOC TIANJIN CHEM RES & DESIGN INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411185664.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The prior art has problems of low conversion, low selectivity and poor catalyst stability when preparing 4,4'-diaminodiphenyl ether, especially in the catalytic hydrogenation process, which has problems of environmental pollution and low production efficiency.

Method used

Using a nano-nickel-based catalyst, it is prepared by a directional uniform precipitation method. The support includes SiO2, MgO, TiO2, Al2O3 and ZrO2. The main active component is nickel and the co-active components are Ag, Pd, Pt, Mo, W, Fe and Cu. , combined with gas-liquid high-efficiency disperser and continuous liquid phase hydrogenation reaction process, achieve efficient 4,4'-dinitroblast ether conversion.

Benefits of technology

Under mild process conditions, the high conversion rate and high selectivity of 4,4'-diaminodiphenyl ether are achieved, with good catalyst stability, few side reactions, low energy consumption, environmentally friendly, and safe and reliable operation of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215918A_ABST
    Figure CN119215918A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, and discloses a nano nickel-based catalyst as well as a preparation method and application thereof. The nano nickel-based catalyst comprises a carrier, a main active component and an auxiliary active component, the carrier contains at least two of SiO2, MgO, TiO2, Al2O3 and ZrO2, the main active component is nickel, and the auxiliary active component is at least one of Ag, Pd, Pt, Mo, W, Fe and Cu; based on the total weight of the nano nickel-based catalyst, the content of the main active component is 15-60%, the content of the auxiliary active component is 0.01-0.2%, and the balance is the carrier. The nano nickel-based catalyst has excellent hydrogenation activity and selectivity under mild reaction process conditions, the conversion rate of 4, 4 '-dinitrodiphenyl ether can reach 100%, the selectivity of 4, 4'-diaminodiphenyl ether can reach 99.8%, the single-pass yield of the target product is high, side reactions are extremely few, the stability is high, the conversion rate is still 99.9% or above after the reaction is performed for 1000 h, and the catalyst is suitable for industrial production. And the selectivity can still be maintained at 99.5% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a nano nickel-based catalyst and a preparation method and application thereof. Background Art

[0002] 4,4'-Diaminodiphenyl ether (ODA for short) is a high value-added fine organic product. It is one of the important raw materials for preparing new engineering materials such as polyimide, polyamide resin, polymaleimide and other heat-resistant high-temperature insulating resin polymer materials. It can also be used as a raw material and cross-linking agent for heat-resistant epoxy resin, polyurethane and other polymer compounds. It is also used to replace carcinogenic benzidine in the production of azo dyes, reactive dyes and fragrances. With the increasing maturity of polyimide product development technology, 4,4'-diaminodiphenyl ether has attracted much attention as an important raw material.

[0003] In industry, 4,4'-diaminodiphenyl ether is usually prepared by reduction reaction using 4,4'-dinitrodiphenyl ether (DNDPE) as raw material. The preparation process mainly includes iron powder ammonium chloride reduction method, hydrazine hydrate reduction method and catalytic hydrogenation method. The iron powder ammonium chloride reduction method is gradually eliminated due to its low product yield of about 75%, high process labor intensity, and the need to discharge a large amount of three wastes. The hydrazine hydrate reduction method uses ethanol as solvent and hydrazine hydrate as hydrogen donor and reducing agent. The yield of this method is high, up to about 90%, and the reaction conditions are relatively mild; however, this method requires the consumption of a large amount of hydrazine hydrate, which is costly, and the process is highly corrosive to equipment, the production process is highly toxic, and there are greater safety risks. The catalytic hydrogenation method has a simple process and low cost. It uses hydrogen as a reducing agent and carries out hydrogenation reaction under the action of a catalyst. The product yield can generally reach more than 90%, which is currently the most ideal production method for ODA. The commonly used catalysts in this method include precious metal catalysts and skeleton nickel catalysts. Supported palladium, platinum and other precious metal catalysts have high hydrogenation activity, but are expensive and prone to carbon deposition; Raney nickel catalyst is a commonly used non-precious metal catalyst in this field. This type of catalyst is low-priced and highly active, but a large amount of caustic soda is required to extract aluminum during preparation, which will cause serious environmental pollution; at the same time, this catalyst is mostly used in intermittent kettle reaction systems. Due to the intense heat release of hydrogenation of nitro compounds, this system has the problems of high danger, low production efficiency, and difficulty in separating catalysts from products. Therefore, it is crucial to develop a green and safe process route with high product quality and excellent performance catalysts to meet industry needs. So far, there has been no report on the use of nano nickel-based catalysts prepared by metal-induced directional precipitation method for the preparation of 4,4'-diaminodiphenyl ether by fixed bed continuous liquid phase hydrogenation. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of low conversion rate, low selectivity and poor catalyst stability in the preparation of 4,4'-diaminodiphenyl ether in the prior art, and to provide a nano nickel-based catalyst and a preparation method and application thereof. The nano nickel-based catalyst of the present invention realizes the preparation of 4,4'-diaminodiphenyl ether by continuous liquid phase hydrogenation of 4,4'-dinitrodiphenyl ether under mild process conditions, and has the characteristics of high conversion rate, high selectivity and good stability.

[0005] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a nano nickel-based catalyst, which includes a carrier, a main active component and an auxiliary active component, the carrier contains at least two of SiO2, MgO, TiO2, Al2O3 and ZrO2, the main active component is nickel, and the auxiliary active component is at least one of Ag, Pd, Pt, Mo, W, Fe and Cu; based on the total weight of the nano nickel-based catalyst, the content of the main active component is 15-60%, the content of the auxiliary active component is 0.01-0.2%, and the balance is the carrier.

[0006] The second aspect of the present invention provides a method for preparing a nano nickel-based catalyst, the method comprising the following steps: (1) mixing an oxide, nitric acid, a citric acid solution, a binder and a molding aid into a dough-like state, extruding the mixture, and then performing a first drying and a first calcination to obtain a nano nickel-based catalyst carrier; (2) mixing the nano nickel-based catalyst carrier, the auxiliary active component salt and the solvent, separating a solid phase from the obtained mixture, and performing a second drying and a second calcination on the solid phase to obtain a nano nickel-based catalyst precursor; (3) The nano nickel-based catalyst precursor is mixed with a mixed solution of a nickel salt and a stabilizer, followed by a reduction reaction.

[0007] Preferably, the process of mixing oxides, nitric acid, citric acid solution, binder and molding aid comprises: kneading the oxides by a kneading machine, and then adding nitric acid, citric acid solution, binder and molding aid and kneading.

[0008] Preferably, in step (1), the oxide is at least two of SiO2, MgO, TiO2, Al2O3 and ZrO2.

[0009] Preferably, in step (1), the binder is alumina and / or silica sol.

[0010] Preferably, in step (1), the molding aid is at least two of sesbania powder, graphite and methyl cellulose.

[0011] Preferably, in step (1), the concentration of nitric acid is 2-4 wt %.

[0012] Preferably, in step (1), the concentration of the citric acid solution is 1.5-2.5 wt %.

[0013] Preferably, in step (1), the usage ratio of the oxide, the nitric acid, the citric acid solution, the binder and the molding aid is (70-200) g: 50 mL: (40-60) mL: (25-45) g: (5-8) g.

[0014] Preferably, in step (1), the first drying conditions include: temperature of 100-140° C. and time of 3-6 h.

[0015] Preferably, in step (1), the first calcination conditions include: temperature of 500-600° C. and time of 3-6 h.

[0016] Preferably, in step (2), the auxiliary active component salt is at least one of a water-soluble silver salt, a palladium salt, a platinum salt, a cobalt salt, a molybdenum salt, a tungsten salt, an iron salt and a copper salt.

[0017] Preferably, the usage ratio of the auxiliary active component salt and the solvent is (0.3-1) g: 300 mL.

[0018] Preferably, the mass ratio of the auxiliary active component salt to the oxide is (0.0017-0.016):1.

[0019] Preferably, in step (2), the second drying conditions include: temperature of 20-30° C. and time of 20-30 h.

[0020] Preferably, in step (2), the conditions for the second calcination include: a temperature of 500-600° C. and a time of 3-6 hours.

[0021] Preferably, in step (3), the nickel salt is nickel nitrate.

[0022] Preferably, the solubility of the nickel salt in the mixed solution of the nickel salt and the stabilizer is 100-305 g / L.

[0023] Preferably, the stabilizer is at least one of ethylenediamine, tartrate and citrate.

[0024] Preferably, the mass ratio of the nickel salt, the stabilizer and the oxide is (1-9):(0.6-6):1.

[0025] Preferably, in step (3), the reduction reaction is carried out by a reducing agent solution, wherein the reducing agent solution contains a reducing agent and a dispersant.

[0026] Preferably, the reducing agent is an inorganic reducing agent and / or an organic reducing agent.

[0027] Preferably, the inorganic reducing agent is at least one of potassium borohydride, sodium borohydride and hydrazine hydrate.

[0028] Preferably, the organic reducing agent is at least one of ethylene glycol, 1,2-propylene glycol and diethylene glycol.

[0029] The third aspect of the present invention provides a nano nickel-based catalyst prepared by the above method.

[0030] The fourth aspect of the present invention provides the use of the above-mentioned nano nickel-based catalyst in the preparation of 4,4'-diaminodiphenyl ether.

[0031] Compared with the prior art, the present invention has the following technical effects: (1) The provided nano nickel-based catalyst is prepared by a directional uniform precipitation method. Compared with the catalyst prepared by the traditional precipitation method, the active components are more evenly dispersed and the active specific surface area is larger. It has excellent hydrogenation activity and selectivity under milder reaction process conditions. The conversion rate of 4,4'-dinitrodiphenyl ether can reach 100%, and the selectivity of 4,4'-diaminodiphenyl ether can reach more than 99.8%. The single-pass yield of the target product is high, and side reactions rarely occur. (2) The provided nano nickel-based catalyst has stable performance and long service life. Under harsh reaction process conditions, the selectivity can still be maintained above 99% after a life test of 1000 hours; (3) The gas-liquid high-efficiency disperser utilizes the high-speed flow of liquid to shear hydrogen and disperse the hydrogen into microbubbles of 1 to 100 microns. The microbubbles have a low flow rate, high solubility, and strong stability, which promotes the dissolution and dispersion of hydrogen and increases the reaction rate. (4) The continuous liquid phase hydrogenation reaction process can achieve efficient conversion of raw materials under low temperature and low pressure conditions. The reaction temperature is 20-30°C lower than that of the intermittent kettle reaction under the action of skeletal nickel catalyst, thereby reducing production energy consumption; reducing the occurrence of side reactions and the difficulty of product post-processing; and achieving long-term stable and safe operation of the device, with low equipment investment cost and no environmental pollution during the catalyst production process, which has significant advantages. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a stability test diagram of the nano nickel-based catalyst of the present invention in catalyzing the hydrogenation of 4,4'-dinitrodiphenyl ether to prepare 4,4'-diaminodiphenyl ether. DETAILED DESCRIPTION

[0033] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0034] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0035] The nano nickel-based catalyst of the present invention comprises a carrier, a main active component and an auxiliary active component, wherein the carrier contains at least two of SiO2, MgO, TiO2, Al2O3 and ZrO2, the main active component is nickel, and the auxiliary active component is at least one of Ag, Pd, Pt, Mo, W, Fe and Cu; based on the total weight of the nano nickel-based catalyst, the content of the main active component is 15-60%, the content of the auxiliary active component is 0.01-0.2%, and the balance is the carrier.

[0036] The present invention also provides a method for preparing a nano nickel-based catalyst, the method comprising the following steps: (1) mixing an oxide, nitric acid, a citric acid solution, a binder and a molding aid into a dough-like state, extruding the mixture, and then performing a first drying and a first calcination to obtain a nano nickel-based catalyst carrier; (2) mixing the nano nickel-based catalyst carrier, the auxiliary active component salt and the solvent, separating a solid phase from the obtained mixture, and performing a second drying and a second calcination on the solid phase to obtain a nano nickel-based catalyst precursor; (3) The nano nickel-based catalyst precursor is mixed with a mixed solution of a nickel salt and a stabilizer, followed by a reduction reaction.

[0037] In the method described in the present invention, the process of mixing oxides, nitric acid, citric acid solution, binder and molding aid may include: kneading the oxides through a kneader, then adding nitric acid, citric acid solution, binder and molding aid and kneading.

[0038] In the method of the present invention, in step (1), the oxide may be at least two of SiO2, MgO, TiO2, Al2O3 and ZrO2.

[0039] In the method of the present invention, in step (1), the binder may be alumina and / or silica sol, preferably alumina.

[0040] In the method of the present invention, in step (1), the molding aid may be at least two of sesbania powder, graphite and methyl cellulose, preferably sesbania powder and graphite.

[0041] In the method of the present invention, in step (1), the concentration of the nitric acid can be 2-4 wt %.

[0042] In the method described in the present invention, in step (1), the concentration of the citric acid solution can be 1.5-2.5wt%.

[0043] In the method described in the present invention, in step (1), the usage ratio of the oxide, the nitric acid, the citric acid solution, the binder and the molding aid can be (70-200) g: 50 mL: (40-60) mL: (25-45) g: (5-8) g.

[0044] In the method of the present invention, in step (1), the first drying conditions include: the temperature can be 100-140°C, preferably 120-130°C; the time can be 3-6h, preferably 3-5h.

[0045] In the method of the present invention, in step (1), the first calcination conditions may include: a temperature of 500-600° C. and a time of 3-6 hours.

[0046] In the method described in the present invention, in step (2), the auxiliary active component salt can be at least one of water-soluble silver salts, palladium salts, platinum salts, cobalt salts, molybdenum salts, tungsten salts, iron salts and copper salts, preferably silver nitrate, sodium tungstate and copper nitrate.

[0047] In the method of the present invention, the usage ratio of the auxiliary active component salt and the solvent can be (0.3-1) g: 300 mL.

[0048] In the method of the present invention, the mass ratio of the auxiliary active component salt to the oxide can be (0.0017-0.016):1.

[0049] In the method of the present invention, in step (2), the second drying conditions may include: a temperature of 20-30° C. and a time of 20-30 h.

[0050] In the method of the present invention, in step (2), the conditions of the second calcination may include: a temperature of 300-500° C. and a time of 3-6 hours.

[0051] In the method of the present invention, in step (3), the nickel salt may be nickel nitrate.

[0052] In the method of the present invention, the solubility of the nickel salt in the mixed solution of the nickel salt and the stabilizer can be 100-305 g / L.

[0053] In the method of the present invention, the stabilizer may be at least one of ethylenediamine, tartrate and citrate, preferably ethylenediamine.

[0054] In the method of the present invention, the mass ratio of the nickel salt, the stabilizer and the oxide can be (1-9): (0.6-6):1.

[0055] In the method of the present invention, in step (3), the reduction reaction is carried out by a reducing agent solution, and the reducing agent solution may contain a reducing agent and a dispersant.

[0056] In the method of the present invention, the reducing agent may be an inorganic reducing agent and / or an organic reducing agent.

[0057] In the method of the present invention, the inorganic reducing agent may be at least one of potassium borohydride, sodium borohydride and hydrazine hydrate, preferably potassium borohydride.

[0058] In the method of the present invention, the organic reducing agent may be at least one of ethylene glycol, 1,2-propylene glycol and diethylene glycol, preferably ethylene glycol.

[0059] In the method of the present invention, the solvent of the reducing agent solution is at least one of deionized water, ethanol and propanol. The concentration of the reducing agent in the reducing agent solution is 0.1 mol / L-2.0 mol / L. The concentration of the dispersant in the reducing agent solution is 0.01%-5%.

[0060] The invention also provides a nano nickel-based catalyst prepared by the method.

[0061] The present invention also provides the use of the nano nickel-based catalyst in the preparation of 4,4'-diaminodiphenyl ether.

[0062] In the application of the present invention, the process of preparing 4,4'-diaminodiphenyl ether may include: (1) Activation of nano nickel-based catalyst: liquid phase activation method is adopted for activation. The nano nickel-based catalyst is loaded into the hydrogenation reactor. The reaction raw materials are fed into the heater by the feed pump and preheated to 110-150°C. Then, they are intensively mixed with fresh hydrogen in the gas-liquid high-efficiency disperser at the bottom of the hydrogenation reactor, so that the sparingly soluble hydrogen forms a large number of microbubbles in the reaction raw materials, forming a uniformly dispersed gas-liquid mixture. The gas-liquid mixture enters the hydrogenation reactor through the liquid distributor at the bottom of the hydrogenation reactor to activate the nano nickel-based catalyst. The activation time is 24-48 hours. (2) Continuous liquid phase hydrogenation reaction process: After the activation of the nano nickel-based catalyst is completed, the process conditions of hydrogenation reaction are switched to the following controlled reaction conditions: reaction temperature 40-90°C, pressure 0.5-3.0 MPa, space velocity 0.5-1.0 h -1 , hydrogen: raw material volume ratio = 0.1-20; the raw material is a mixture of 4,4'-dinitrodiphenyl ether and a solvent, the solvent is one of toluene, N,N-dimethylformamide and N,N-dimethylacetamide, and the mass ratio of 4,4'-dinitrodiphenyl ether to the solvent is 1:19-1.5:1; the reaction product is analyzed by gas chromatography. In this article, the pressure is gauge pressure.

[0063] The nano nickel-based catalyst and its preparation method and application described in the present invention are further illustrated by examples. The examples are implemented based on the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following examples.

[0064] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.

[0065] Example 1 Preparation of nano nickel-based catalyst: (1) Weigh 100 g of MgO and 70 g of TiO2 and mix them evenly in a kneader, then add 50 mL of 3 wt% nitric acid, 50 mL of 2 wt% citric acid, 30 g of Al2O3, 3 g of sesbania powder and 3 g of graphite, continue kneading until the mixed raw materials are in a dough-like state, extrude and shape them into clover-shaped strips with a diameter of 2.5 mm, then dry them at a temperature of 120°C for 4 h and calcine them at a temperature of 550°C for 4 h to obtain a nano nickel-based catalyst carrier; (2) Weighing 0.30 g of silver nitrate and dissolving it in 300 mL of deionized water to prepare a salt solution of an active component, immersing the nano nickel-based catalyst carrier in the salt solution of the active component at a temperature of 25° C. and a stirring rate of 200 rpm, stirring for 3 h, removing most of the water by suction filtration, and drying the obtained filter cake at a temperature of 25° C. for 24 h and calcining at a temperature of 550° C. for 4 h to obtain a nano nickel-based catalyst precursor; (3) 201.11 g of Ni(NO3)2·6H2O was weighed and dissolved in 2 L of deionized water, and 137.16 g of ethylenediamine was added. The mixture was stirred at a temperature of 30 °C and a stirring rate of 200 rpm to form a stable solution. 82.26 g of potassium borohydride and 3.8 g of polyvinyl alcohol were weighed and dissolved in 1 L of deionized water to prepare a reducing solution. The catalyst precursor was slowly added to the stable solution. The mixture was stirred and mixed at a temperature of 40 °C and a stirring rate of 200 rpm for 0.5 h. The reducing solution was then added at a uniform speed using a peristaltic pump to react at a temperature of 40 °C. The reaction time was controlled to be 0.5 h. After the reaction was completed, the slurry was filtered, and the product was rinsed with 10 L of deionized water and washed with 2 L of ethanol to obtain a nano nickel-based catalyst. The nano nickel-based catalyst was dried at a temperature of 25 °C for 12 h and then sealed for storage. The mass proportions of the main active component and the auxiliary active component in the nano nickel-based catalyst are recorded in Table 1.

[0066] Preparation of 4,4'-diaminodiphenyl ether catalyzed by nano nickel-based catalyst: (1) Activation of nano nickel-based catalyst: Activation was performed by liquid phase activation method. 40 mL of the nano nickel-based catalyst prepared in Example 1 was loaded into the hydrogenation reactor. The reaction raw materials were fed into the heater by a feed pump and preheated to 110°C. Then, they were intensively mixed with fresh hydrogen in the gas-liquid high-efficiency disperser at the bottom of the hydrogenation reactor to form a uniformly dispersed gas-liquid mixture. The gas-liquid mixture entered the hydrogenation reactor through the liquid distributor at the bottom of the hydrogenation reactor to activate the catalyst. The activation time was 24 hours. (2) Continuous liquid phase hydrogenation reaction process: After the activation of the nano nickel-based catalyst, switch to the hydrogenation reaction process conditions, and control the reaction process conditions as follows: reaction temperature of 40 °C, reaction pressure of 0.5 MPa, and space velocity of 0.7 h -1 The volume ratio of hydrogen and 4,4'-dinitrodiphenyl ether was 2, the raw material was a mixture of 4,4'-dinitrodiphenyl ether and toluene, and the mass ratio of 4,4'-dinitrodiphenyl ether and toluene was 1:2. After 24 hours of reaction, samples were taken and analyzed by gas chromatography. The conversion rate of 4,4'-dinitrodiphenyl ether (DNDPE) and the selectivity of 4,4'-diaminodiphenyl ether (ODA) were recorded in Table 1.

[0067] Example 2 Preparation of nano nickel-based catalyst: (1) Weigh 85 g of MgO and 100 g of TiO2 and mix them evenly in a kneader, then add 50 mL of 3 wt% nitric acid, 50 mL of 2 wt% citric acid, 45 g of Al2O3, 3 g of sesbania powder and 3 g of graphite, continue kneading until the mixed raw materials are in a dough-like state, extrude and shape them into clover-shaped strips with a diameter of 2.5 mm, then dry them at a temperature of 120°C for 4 h and calcine them at a temperature of 550°C for 4 h to obtain a nano nickel-based catalyst carrier; (2) Weigh 0.5430 g of sodium tungstate dihydrate and dissolve it in 300 mL of deionized water to prepare a salt solution of the auxiliary active component, immerse the nano nickel-based catalyst carrier in the salt solution of the auxiliary active component at a temperature of 25° C. and a stirring rate of 300 rpm, stir for 3 h, remove most of the water by suction filtration, dry the obtained filter cake at a temperature of 25° C. for 24 h and calcine at a temperature of 550° C. for 4 h to obtain a nano nickel-based catalyst precursor; (3) 613.62 g of Ni(NO3)2·6H2O was weighed and dissolved in 2 L of deionized water, and 418.49 g of ethylenediamine was added. The mixture was stirred at a temperature of 30 °C and a stirring rate of 300 rpm to form a stable solution. 14.52 g of potassium borohydride, 31 g of ethylene glycol and 11.6 g of polyvinyl alcohol were weighed and dissolved in 1 L of deionized water to prepare a reducing solution. The catalyst precursor was slowly added to the stable solution. The mixture was stirred and mixed at a temperature of 30 °C and a stirring rate of 300 rpm for 1.0 h. The reducing solution was then added at a constant speed using a peristaltic pump to react at a temperature of 50 °C. The reaction time was controlled to be 0.5 h. After the reaction was completed, the slurry was filtered, and the product was rinsed with 10 L of deionized water and washed with 2 L of ethanol to obtain a nano nickel-based catalyst. The nano nickel-based catalyst was dried at a temperature of 25 °C for 24 h and then sealed for storage. The mass proportions of the main active component and the auxiliary active component in the nano nickel-based catalyst are recorded in Table 1.

[0068] Preparation of 4,4'-diaminodiphenyl ether catalyzed by nano nickel-based catalyst: (1) Activation of nano nickel-based catalyst: Activation was performed by liquid phase activation method. 40 mL of the nano nickel-based catalyst prepared in Example 2 was loaded into the hydrogenation reactor. The reaction raw materials were fed into the heater by a feed pump and preheated to 140°C. Then, they were intensively mixed with fresh hydrogen in the gas-liquid high-efficiency disperser at the bottom of the hydrogenation reactor to form a uniformly dispersed gas-liquid mixture. The gas-liquid mixture entered the hydrogenation reactor through the liquid distributor at the bottom of the hydrogenation reactor to activate the catalyst. The activation time was 24 hours. (2) Continuous liquid phase hydrogenation reaction process: After the activation of the nano nickel-based catalyst, switch to the hydrogenation reaction process conditions, and control the reaction process conditions as follows: reaction temperature of 40 °C, reaction pressure of 0.5 MPa, and space velocity of 0.7 h -1The volume ratio of hydrogen and 4,4'-dinitrodiphenyl ether was 5, the raw material was a mixture of 4,4'-dinitrodiphenyl ether and toluene, and the mass ratio of 4,4'-dinitrodiphenyl ether and toluene was 1:2. After 24 hours of reaction, samples were taken and analyzed by gas chromatography. The conversion rate of 4,4'-dinitrodiphenyl ether (DNDPE) and the selectivity of 4,4'-diaminodiphenyl ether (ODA) were recorded in Table 1.

[0069] Example 3 Preparation of nano nickel-based catalyst: (1) 85 g of SiO2 and 50 g of TiO2 were weighed and mixed in a kneader, followed by adding 40 mL of nitric acid with a concentration of 2 wt%, 40 mL of citric acid with a concentration of 1.5 wt%, 45 g of Al2O3, 2 g of sesbania powder and 3 g of graphite, and kneading was continued until the mixed raw materials were in a dough shape, extruded into clover strips with a diameter of 2.5 mm, and then dried at a temperature of 130° C. for 3 h and calcined at a temperature of 500° C. for 3 h to obtain a nano nickel-based catalyst carrier; (2) Weighing 0.5430 g of sodium tungstate dihydrate and dissolving it in 300 mL of deionized water to prepare a salt solution of the auxiliary active component, immersing the nano nickel-based catalyst carrier in the salt solution of the auxiliary active component at a temperature of 25° C. and a stirring rate of 450 rpm, stirring for 3 h, removing most of the water by suction filtration, and drying the obtained filter cake at a temperature of 20° C. for 20 h and calcining at a temperature of 500° C. for 3 h to obtain a nano nickel-based catalyst precursor; (3) 613.62 g of Ni(NO3)2·6H2O was weighed and dissolved in 2 L of deionized water, and 418.49 g of ethylenediamine was added. The mixture was stirred at a temperature of 45°C and a stirring rate of 450 rpm to form a stable solution. 14.52 g of potassium borohydride, 31 g of ethylene glycol and 11.6 g of polyvinyl alcohol were weighed and dissolved in a mixed solvent of ethanol and deionized water in a volume ratio of 1:1 (the volume of the solvent was 1 L) to prepare a reducing solution. The catalyst precursor was slowly added to the stable solution. The mixture was stirred at a temperature of 30°C and a stirring rate of 450 rpm. The mixture was stirred and mixed at a rate of 450 rpm for 1.0 h, and then a reducing solution was added at a uniform speed using a peristaltic pump to react at a temperature of 60°C. The reaction time was controlled to be 0.5 h. After the reaction, the slurry was filtered, and the product was rinsed with 10 L of deionized water and 2 L of ethanol to obtain a nano-nickel-based catalyst. The nano-nickel-based catalyst was dried at a temperature of 25°C for 24 h and then sealed for storage. The mass proportions of the main active component and the auxiliary active component in the nano-nickel-based catalyst are recorded in Table 1.

[0070] Preparation of 4,4'-diaminodiphenyl ether catalyzed by nano nickel-based catalyst: (1) Activation of nano nickel-based catalyst: Activation was performed by liquid phase activation method. 40 mL of the nano nickel-based catalyst prepared in Example 3 was loaded into the hydrogenation reactor. The reaction raw materials were fed into the heater by a feed pump and preheated to 140°C. Then, they were intensively mixed with fresh hydrogen in the gas-liquid high-efficiency disperser at the bottom of the hydrogenation reactor to form a uniformly dispersed gas-liquid mixture. The gas-liquid mixture entered the hydrogenation reactor through the liquid distributor at the bottom of the hydrogenation reactor to activate the catalyst. The activation time was 24 hours. (2) Continuous liquid phase hydrogenation reaction process: After the activation of the nano nickel-based catalyst, switch to the hydrogenation reaction process conditions, and control the reaction process conditions as follows: reaction temperature of 50 °C, reaction pressure of 1.0 MPa, and space velocity of 0.7 h -1 The volume ratio of hydrogen and 4,4'-dinitrodiphenyl ether was 5, the raw material was a mixture of 4,4'-dinitrodiphenyl ether and toluene, and the mass ratio of 4,4'-dinitrodiphenyl ether and toluene was 1:2. After 24 hours of reaction, samples were taken and analyzed by gas chromatography. The conversion rate of 4,4'-dinitrodiphenyl ether (DNDPE) and the selectivity of 4,4'-diaminodiphenyl ether (ODA) were recorded in Table 1.

[0071] Example 4 Preparation of nano nickel-based catalyst: (1) Weigh 50 g of ZrO2 and 20 g of Al2O3 and mix them evenly in a kneader, then add 60 mL of 4 wt% nitric acid, 60 mL of 2.5 wt% citric acid, 25 g of Al2O3, 4 g of sesbania powder and 4 g of graphite, continue kneading until the mixed raw materials are in a dough-like state, extrude and mold into clover-shaped strips with a diameter of 2.5 mm, then dry at 120°C for 6 h and calcine at 600°C for 6 h to obtain a nano nickel-based catalyst carrier; (2) Weigh 0.3530 g of sodium tungstate dihydrate and 0.574 g of copper nitrate trihydrate and dissolve them in 300 mL of deionized water to prepare a salt solution of the auxiliary active component, immerse the nano nickel-based catalyst carrier in the salt solution of the auxiliary active component at a temperature of 60° C. and a stirring rate of 450 rpm, stir for 3 h, remove most of the water by suction filtration, and then dry the obtained filter cake at a temperature of 30° C. for 30 h and calcine at a temperature of 600° C. for 6 h to obtain a nano nickel-based catalyst precursor; (3) Weigh 613.62 g of Ni(NO3)2·6H2O and dissolve it in 2 L of deionized water. Add 418.49 g of ethylenediamine and stir at 60 °C and 450 rpm to form a stable solution. Weigh 14.52 g of potassium borohydride, 31 g of ethylene glycol and 11.6 g of polyvinyl alcohol and dissolve them in a mixed solvent of ethanol and deionized water in a volume ratio of 1:1 (solvent volume of 1 L) to prepare a reducing solution. Slowly add the catalyst precursor to the stable solution and stir at 25 °C and 450 rpm. The mixture was stirred and mixed at a rate of 450 rpm for 1.0 h, and then a reducing solution was added at a uniform speed using a peristaltic pump to react at a temperature of 70°C. The reaction time was controlled to be 0.5 h. After the reaction, the slurry was filtered, and the product was rinsed with 10 L of deionized water and 2 L of ethanol to obtain a nano-nickel-based catalyst. The nano-nickel-based catalyst was dried at a temperature of 25°C for 48 h and then sealed for storage. The mass proportions of the main active component and the auxiliary active component in the nano-nickel-based catalyst are recorded in Table 1.

[0072] Preparation of 4,4'-diaminodiphenyl ether catalyzed by nano nickel-based catalyst: (1) Activation of nano nickel-based catalyst: Activation was performed by liquid phase activation method. 40 mL of nano nickel-based catalyst prepared in Example 4 was loaded into the hydrogenation reactor. The reaction raw materials were fed into the heater by a feed pump and preheated to 140°C. Then, they were intensively mixed with fresh hydrogen in the gas-liquid high-efficiency disperser at the bottom of the hydrogenation reactor to form a uniformly dispersed gas-liquid mixture. The gas-liquid mixture entered the hydrogenation reactor through the liquid distributor at the bottom of the hydrogenation reactor to activate the catalyst. The activation time was 24 hours. (2) Continuous liquid phase hydrogenation reaction process: After the activation of the nano nickel-based catalyst, switch to the hydrogenation reaction process conditions, and control the reaction process conditions as follows: reaction temperature of 50 °C, reaction pressure of 1.0 MPa, and space velocity of 1.0 h -1 The volume ratio of hydrogen and 4,4'-dinitrodiphenyl ether was 10, the raw material was a mixture of 4,4'-dinitrodiphenyl ether and toluene, and the mass ratio of 4,4'-dinitrodiphenyl ether and toluene was 1:2. After 24 hours of reaction, samples were taken and analyzed by gas chromatography. The conversion rate of 4,4'-dinitrodiphenyl ether (DNDPE) and the selectivity of 4,4'-diaminodiphenyl ether (ODA) were recorded in Table 1.

[0073] Comparative Example 1 4,4'-diaminodiphenyl ether was prepared by catalysis according to the method of Example 4, except that the nano nickel-based catalyst prepared in Example 4 was replaced with a commercially available skeleton nickel catalyst (in the skeleton nickel catalyst, the mass fraction of Ni was 90.81%, and the mass fraction of Al2O3 was 4%). The results are shown in Table 1.

[0074] Test example: In the process of preparing 4,4'-diaminodiphenyl ether catalyzed by the nano nickel-based catalyst prepared in Examples 1-4 and Comparative Example 1, the conversion rate of 4,4'-dinitrodiphenyl ether (DNDPE) and the selectivity of 4,4'-diaminodiphenyl ether (ODA) were measured by gas chromatography, referring to the national standard GB / T 9722-2023 "General Rules for Gas Chromatography of Chemical Reagents".

[0075] Table 1

[0076] It can be seen from the results in Table 1 that the nano nickel-based catalyst of the present invention has excellent hydrogenation activity and selectivity under milder reaction process conditions, the conversion rate of 4,4'-dinitrodiphenyl ether can reach 100%, the selectivity of 4,4'-diaminodiphenyl ether can reach 99.8%, the single-pass yield of the target product is high, and side reactions rarely occur.

[0077] Stability test: (1) 40 mL of the nano nickel-based catalyst prepared in Example 2 was loaded into a hydrogenation reactor. The reaction raw materials were fed into a heater by a feed pump and preheated to 140° C., and then intensively mixed with fresh hydrogen in a gas-liquid high-efficiency disperser at the bottom of the hydrogenation reactor to form a uniformly dispersed gas-liquid mixture. The gas-liquid mixture entered the hydrogenation reactor through a liquid distributor at the bottom of the hydrogenation reactor to activate the catalyst. The activation time was 24 h. (2) Continuous liquid phase hydrogenation reaction process: After the activation of the nano nickel-based catalyst, switch to the hydrogenation reaction process conditions, and control the reaction process conditions as follows: reaction temperature of 50 °C, reaction pressure of 1.0 MPa, and space velocity of 1.0 h -1 The volume ratio of hydrogen to 4,4'-dinitrodiphenyl ether was 10, the raw material was a mixture of 4,4'-dinitrodiphenyl ether and toluene, the mass ratio of 4,4'-dinitrodiphenyl ether to toluene was 1:2, the reaction time was 1000 h, samples were taken every 12 h and analyzed by gas chromatography, and the conversion rate of 4,4'-dinitrodiphenyl ether (DNDPE) and the selectivity of 4,4'-diaminodiphenyl ether (ODA) were recorded, such as Figure 1 shown.

[0078] from Figure 1 It can be seen that after 1000 hours of stability investigation experiment on DNDPE hydrogenation to prepare ODA, the DNDPE conversion rate still remained above 99.8%, the ODA selectivity still remained above 99.5%, and the device operation was stable.

[0079] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A nano nickel-based catalyst, characterized in that: The nano nickel-based catalyst comprises a carrier, a main active component and an auxiliary active component, wherein the carrier contains at least two of SiO2, MgO, TiO2, Al2O3 and ZrO2, the main active component is nickel, and the auxiliary active component is at least one of Ag, Pd, Pt, Mo, W, Fe and Cu; based on the total weight of the nano nickel-based catalyst, the content of the main active component is 15-60%, the content of the auxiliary active component is 0.01-0.2%, and the balance is the carrier.

2. A method for preparing a nano nickel-based catalyst, characterized in that: The method comprises the following steps: (1) mixing an oxide, nitric acid, a citric acid solution, a binder and a molding aid into a dough-like state, extruding the mixture, and then performing a first drying and a first calcination to obtain a nano nickel-based catalyst carrier; (2) mixing the nano nickel-based catalyst carrier, the auxiliary active component salt and the solvent, separating a solid phase from the obtained mixture, and performing a second drying and a second calcination on the solid phase to obtain a nano nickel-based catalyst precursor; (3) The nano nickel-based catalyst precursor is mixed with a mixed solution of a nickel salt and a stabilizer, followed by a reduction reaction.

3. The method according to claim 2, characterized in that The process of mixing oxides, nitric acid, citric acid solution, binder and molding aid comprises: kneading the oxides by a kneading machine, then adding nitric acid, citric acid solution, binder and molding aid and kneading.

4. The method according to claim 2 or 3, characterized in that: In step (1), the oxide is at least two of SiO2, MgO, TiO2, Al2O3 and ZrO2; Preferably, in step (1), the binder is alumina and / or silica sol; Preferably, in step (1), the molding aid is at least two of sesbania powder, graphite and methyl cellulose; Preferably, in step (1), the concentration of nitric acid is 2-4wt%; Preferably, in step (1), the concentration of the citric acid solution is 1.5-2.5wt%; Preferably, in step (1), the usage ratio of the oxide, the nitric acid, the citric acid solution, the binder and the molding aid is (70-200) g: 50 mL: (40-60) mL: (25-45) g: (5-8) g; Preferably, in step (1), the first drying conditions include: temperature of 100-140°C and time of 3-6h; Preferably, in step (1), the first calcination conditions include: temperature of 500-600° C. and time of 3-6 h.

5. The method according to any one of claims 2 to 4, characterized in that: In step (2), the auxiliary active component salt is at least one of a water-soluble silver salt, a palladium salt, a platinum salt, a cobalt salt, a molybdenum salt, a tungsten salt, an iron salt and a copper salt; Preferably, the ratio of the auxiliary active component salt to the solvent is (0.3-1) g: 300 mL; Preferably, the mass ratio of the auxiliary active component salt to the oxide is (0.0017-0.016):

1.

6. The method according to any one of claims 2 to 5, characterized in that: In step (2), the second drying conditions include: temperature of 20-30°C and time of 20-30h; Preferably, in step (2), the conditions for the second calcination include: a temperature of 500-600° C. and a time of 3-6 hours.

7. The method according to any one of claims 2 to 6, characterized in that: In step (3), the nickel salt is nickel nitrate; Preferably, the solubility of the nickel salt in the mixed solution of the nickel salt and the stabilizer is 100-305 g / L; Preferably, the stabilizer is at least one of ethylenediamine, tartrate and citrate; Preferably, the mass ratio of the nickel salt, the stabilizer and the oxide is (1-9):(0.6-6):

1.

8. The method according to any one of claims 2 to 7, characterized in that: In step (3), the reduction reaction is carried out by a reducing agent solution, wherein the reducing agent solution contains a reducing agent and a dispersant; Preferably, the reducing agent is an inorganic reducing agent and / or an organic reducing agent; Preferably, the inorganic reducing agent is at least one of potassium borohydride, sodium borohydride and hydrazine hydrate; Preferably, the organic reducing agent is at least one of ethylene glycol, 1,2-propylene glycol and diethylene glycol.

9. A nano nickel-based catalyst prepared by the method described in any one of claims 2 to 8.

10. Use of the nano nickel-based catalyst according to claim 1 or 9 in the preparation of 4,4'-diaminodiphenyl ether.